2016
DOI: 10.1055/s-0036-1594258
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Approach of a Proximal Anterior Inferior Cerebellar Artery Aneurysm: Case Report

Abstract: Anterior inferior cerebellar artery (AICA) aneurysms are extremely rare, accounting for only 0.75% of all intracranial aneurysms. The average age of patients suffering from those aneurysms found in the literature was 44 years, with no significant difference between the sexes. These aneurysms can manifest clinically through expansive symptoms in cerebellopontine angle or through signs and symptoms of subarachnoid hemorrhage, such as nausea, vomiting, headache, nystagmus and paresis. The gold standard exam for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Few reports suggested that coil embolization and parent artery occlusion (PAO) would be valuable treatment options against dissecting AICA aneurysms. 3 - 6) However, the records of incidence and therapeutics of the dissecting AICA aneurysms in literature are rare. 7 - 9) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports suggested that coil embolization and parent artery occlusion (PAO) would be valuable treatment options against dissecting AICA aneurysms. 3 - 6) However, the records of incidence and therapeutics of the dissecting AICA aneurysms in literature are rare. 7 - 9) …”
Section: Introductionmentioning
confidence: 99%
“…Few reports suggested that coil embolization and parent artery occlusion (PAO) would be valuable treatment options against dissecting AICA aneurysms. [3][4][5][6] However, the records of incidence and therapeutics of the dissecting AICA aneurysms in literature are rare. [7][8][9] In this article, we report a case of dissecting AICA aneurysm treated with PAO, and discuss the therapeutics and literature review of this pathology.…”
Section: Introductionmentioning
confidence: 99%